Feedback evaluation from first year MBBS students on foundation course - Amrita Ghosh; Samudra Guha (Al Ameen Medical College, 2023)
Background: Foundation course is an integral part of MBBS course and curriculum introduced by the National Medical Commission (NMC) that is cogently grounded to bridge conceptual and contextual gap of medical education placed at beginning of curriculum. Objective: This feedback evaluation was conducted on the First year 2019 MBBS students as a part of the foundation course program promulgated by the NMC to get candid reflection. Methods: An unlinked anonymous self-administered pretested open-ended questionnaire on feedback of content and outcome was used on internalization of 169 First year MBBS students regarding the month-long foundation course. Qualitative responses were analyzed on 'overall impression' on the course; 'best', 'worst' and 'unnecessary' parts of the course; lastly open question on 'How the Foundation course could have been better?. Results: Overall agreement on positive aspects was felt on schedule, facilitators, language of teaching, extracurricular activities. Best parts of the course were visits to the departments of College & Hospital including emergency and health centres, Basic Life Support, Immunization, History of Medicine, Taekwondo, Co-curricular physical activities, Communication, Interaction and Dedication of teachers, Cardiopulmonary resuscitation (CPR). Worst parts were Sports, Yoga, language class, strict 75% attendance. Unnecessary parts were Sports, Yoga, English compulsory class; Music, Computer. On 'How the Course could have been better' general comments was addition of subject specific classes and flexible attendance. Conclusions: This feedback analysis deduced acceptance and effectiveness of the course for undergraduate students to help them cope with stressful active professional learning later.